Line broadenings of phosphine perturbed by He revisited. (17th November 2022) - Salem, J.; Salem, M.; Dhib, M.; Ben Younes, R.; Aroui, H.; Hochlaf, M.
ABSTRACT: Recently, advanced ab initio computations were used to generate the three-dimensional potential energy surface (3D-PES) of the phosphine–He (PH3 –He) van der Waals complex along the intermonomer coordinates. This 3D-PES describes correctly the complex features of the intermolecular interactions between PH3 and He, which are on the origin of pressure broadening phenomena. At present, we take advantage of this accurate 3D-PES to compute the phosphine line broadenings perturbed by He at room temperature. First, we adjusted this 3D-PES by a new 'fractional' function in order to be able to incorporated it into our collisional broadening calculation code. Then, we considered the semi-classical model of Modified Robert and Bonamy improved by so-called the notion of exact trajectory to deduce the He-broadening coefficients of phosphine lines at room temperature. Room temperature data are given in the case of different branches of the parallel, ν 2, and perpendicular, ν 4, PH3 vibrational bands. Our results show an improved agreement with the experimental measurements. This work should be of great help for the precise determination of PH3 abundances in planetary atmospheres spectra. GRAPHICAL ABSTRACT: UF0001